Soil Physicochemical Properties, Growth and Development of Sweet Melon (Cucumis melo L.) as Influenced by some Organic Amendments at Awka, South Eastern Nigeria (e-Proceedings of the Faculty of Agriculture International Conference, 2023)
A study on the soil physicochemical properties and agronomy of sweet melon (Cucumis melo L.) as influenced by different organic amendments was conducted at the Soil Science and Land Resources Management Research Farm, Faculty of Agriculture, Nnamdi Azikiwe University, Awka. The experiment was laid out in randomized complete block design (RCBD) with five treatments, replicated three times. The treatments were: Bat manure (10t/ha), Pig manure (10t/ha), Dry neem leaves (10t/ha), Poultry manure (10t/ha), and a control (0t/ha). Data collected were subjected to Analysis of Variance (ANOVA) using Genstat4th edition statistical software. Means were separated usingFisher’s Least Significant Difference (F-LSD) at 5% probability level. The results obtained showed that the application of organic amendments had significant effects on some soil physical properties but did not significantly affect any of the chemical parameters tested. Meanwhile, some growth parameters studied as well as the yield component showed significant differences among the various treatments at 3, 6 and 9weeks after planting (WAP). Bat Guano recorded the highest values for most physical properties, growth parameters and fruit weight, and is closely followed by poultry manure. Though soil chemical properties did not show statistical significant differences, application of organic amendments resulted to increased value of soil organic carbon, Total N, pH, CEC, and exchangeable bases. Bat manure though scarce, is recommended for farmers to be used in the production of Sweet Melon in the study area for higher yield and an alternative manure source for sustainable soil fertility management.
Keywords: Bat Guano; Neem leaves; Organic amendments; Soil physicochemical properties; Sweet melon